Effectiveness of Physical Activity Interventions in Type 2 Diabetes Mellitus Patients: A Literature Review - Suardi Suardi (Alta Dharma Publisher, 2021)
Diabetes Mellitus (DM) is a chronic disease associated with insulin deficiency and the inability of the pancreas to produce enough insulin. WHO predicts that the number of people with type II diabetes mellitus in Indonesia will increase to 12 million in 2030. The study aimed to describe Physical Activity Interventions in type 2 diabetes mellitus patients. Using the online journal database that provides free articles and journals from 2010 -2020 in PDF form such as: Scinapse, Pubmed, ProQuest, MDPI and Google Scholar using the keywords